The structure of the proton and the combination of fundamental forces (International Journal of Scientific Research and Management (IJSRM), 2024)
This publication deals with the structure of the proton and the three fundamental forces: strong force, electromagnetic force and gravitational force. It can be shown that these fundamental forces have an electromagnetic origin.